Bible Study Participation in the Digital Era: Challenges and Opportunities - Ribka Ribka (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines Bible study participation in the digital era, focusing on the main factors that encourage and hinder engagement. Consistent involvement in Bible study is vital for spiritual growth, yet participation often faces challenges. Using a systematic literature review of books and scholarly journals, this research synthesizes findings on internal and external influences. Internal drivers include personal desire to engage with Scripture, spiritual discipline, and intrinsic motivation. External supports such as conducive environments, study tools, and engaging pedagogy also play a role. Conversely, barriers such as time constraints, busy schedules, diminished motivation, and digital distractions impede sustained engagement. The findings highlight the need for contextually relevant and flexible Bible study programs. In the digital era, strategies must balance technological innovation with spiritual discipline to sustain meaningful participation.